Detection and Quantification of β-Amyloid, Pyroglutamyl Aβ, and Tau in Aged Canines. Issue 9 (September 2015) - Schmidt, Franziska; Boltze, Johannes; Jäger, Carsten; Hofmann, Sarah; Willems, Nicole; Seeger, Johannes; Härtig, Wolfgang; Stolzing, Alexandra
Abstract : Abstract: Canine cognitive dysfunction syndrome is an age-associated disorder that resembles many aspects of human Alzheimer disease. The characterization of canine cognitive dysfunction syndrome has been restricted to selected laboratory dogs and mongrels, thereby limiting our knowledge of potential breed-related and age-related differences. We examined the brains of 24 dogs from various breeds. The frontal cortex, hippocampus, and entorhinal cortex were investigated. Deposits of β-amyloid (Aβ) and tau were analyzed phenotypically and quantified stereologically. In all dogs aged 10 years or older, plaques containing pyroglutamyl Aβ and Aβ8–17 were detected. Within the ventral hippocampus, significantly more pyroglutamyl Aβ plaques were deposited in small and medium dogs than in large dogs. Hyperphosphorylated tau with formation of neurofibrillary tangles was observed in 3 animals aged 13 to 15 years. This study provides the first investigation of pyroglutamyl Aβ in comparison with total Aβ (as shown by Aβ8–17 immunoreactivity) in dogs of different breeds, sizes, and ages. Our results indicate that canine cognitive dysfunction syndrome is relatively common among aged canines, thereby emphasizing the relevance of such populations to translational Alzheimer disease research. Abstract : Supplemental Digital Content is available in the text.